(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This paper investigates the restoration of cylindrical parts through a novel combination of surface coating and turning techniques. As cylindrical components are widely used in various industrial applications, their wear and degradation can lead to significant operational challenges and costs. The research focuses on addressing these issues by integrating advanced surface coating methods, such as thermal spraying and chemical vapor deposition, with precision turning processes.